2019
DOI: 10.1111/jep.13096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical frailty screening in geriatric acute care

Abstract: Background: While frailty status is an attractive risk stratification tool, the evaluation of frailty in acute care can be challenging as some inpatients are unable to complete performance-based tests as part of frailty assessment and some tools may lack discriminative ability and categorize majority of cohorts as "frail". In this study, we evaluated the feasibility of frailty screening with the simple clinical frailty scale (CFS) by different clinicians, and its association with mortality and rehospitalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
(55 reference statements)
0
22
1
Order By: Relevance
“…Our study included all patients aged 50 years and older. Furthermore, the discrepancy may be owing to a difference in the time frame of readmissions examined in our study (6 months) compared with the study by Chua et al 16 (12 months).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Our study included all patients aged 50 years and older. Furthermore, the discrepancy may be owing to a difference in the time frame of readmissions examined in our study (6 months) compared with the study by Chua et al 16 (12 months).…”
Section: Discussioncontrasting
confidence: 73%
“…Our study results also indicated that frailty was associated with readmission for falls after index admission. In contrast, a study by Chua et al 16 indicated that frailty status determined using the CHSA CFS was not associated with a higher rate of rehospitalization within 6 months after hospital discharge. However, this discrepancy might be explained by the differences in inclusion and exclusion criteria between the studies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The increased risk experienced by frail older adults who are acutely ill comes not just from their frailty, but from the severity of their illness [ 7 , 13 , 14 ]. Both frailty and illness acuity can add information about risk [ 5 , 6 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One instrument that has been validated in the inpatient setting is the Clinical Frailty Scale (CFS) (Figure 1), which is a simple face to face clinician assessment of frailty status [9]. The CFS can be rapidly scored within a clinical environment and has demonstrated high inter-rater reliability in a range of hospital settings, including the emergency department, intensive care and geriatric acute care [9][10][11][12]. The CFS has been found to predict clinical outcomes including mortality and dependence on health care in a range of settings [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%